2004
DOI: 10.1111/j.1574-6968.2004.tb09693.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-free NisI: interaction with nisin and contribution to nisin immunity via secretion

Abstract: Nisin‐producing Lactococcus lactis cells protect their own cytoplasmic membrane by specific immunity proteins, NisF/E/G and NisI, a transporter complex and a lipoprotein, respectively. A portion of NisI is secreted to the medium in a lipid‐free form (LF‐NisI). Here, kinetics of the interaction between nisin and LF‐NisI was examined by surface plasmon resonance analysis. The affinity constant KD for the interaction was calculated to be in the micromolar range. Contribution of the secreted LF‐NisI to nisin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Both of the forms were shown to bind nisin [52] and, interestingly, lipid-free NisI enhanced immunity of L. lactis more efficiently in the strain expressing nisEFG as compared to the strain lacking these genes. [51]. These findings suggest that lipid-free NisI either supported NisEFG in exporting nisin from the cytoplasmic membrane or NisFEG assisted the effect of lipid-free NisI by providing high local concentrations of nisin close to the cytoplasmic membrane that lipid-free NisI could intercept and by diffusion move away to the environment.…”
Section: Immunity Of Nisin-producing Strainsmentioning
confidence: 82%
See 1 more Smart Citation
“…Both of the forms were shown to bind nisin [52] and, interestingly, lipid-free NisI enhanced immunity of L. lactis more efficiently in the strain expressing nisEFG as compared to the strain lacking these genes. [51]. These findings suggest that lipid-free NisI either supported NisEFG in exporting nisin from the cytoplasmic membrane or NisFEG assisted the effect of lipid-free NisI by providing high local concentrations of nisin close to the cytoplasmic membrane that lipid-free NisI could intercept and by diffusion move away to the environment.…”
Section: Immunity Of Nisin-producing Strainsmentioning
confidence: 82%
“…Subsequently, the protein is anchored to the extracellular side of the cell membrane via lipid modification of the N-terminal cysteine residue [49]. Circular dichroism (CD) studies and biomolecular interaction analysis have provided evidence for physical interaction of nisin and NisI [50,51]. Having no homology to other LanI proteins, purified NisI was demonstrated to bind specifically to nisin but not to subtilin, which is closely related to nisin, using native SDS-PAGE, and to form an insoluble and unstable complex [52].…”
Section: Immunity Of Nisin-producing Strainsmentioning
confidence: 99%
“…Immunity to nisin is provided by a specific immunity protein, NisI, and a specialized ABC transporter, NisFEG (9). The lipoprotein, NisI, most probably orients to the outside of the cytoplasmic membrane and binds nisin, preventing it from binding to lipid II and forming pores in the cell membrane (10,11). NisFEG are thought to transport nisin from the cytoplasmic membrane to the external environment, thus preventing the accumulation of the high number of nisin molecules necessary for pore formation (12,13).…”
mentioning
confidence: 99%
“…About 50% of NisI is bound to the outside of the cell membrane, whereas the other 50% is secreted from the cell (11). The NisI protein, which is not membrane anchored, functions by aggregating nisin extracellularly, thus providing immunity to the host cell (12,13). A study with C-terminally truncated NisI proteins revealed that 21 amino acids located in the C terminus are essential in providing specific immunity to nisin (14).…”
mentioning
confidence: 99%
“…These fusion proteins were capable of providing immunity to nisin when expressed heterologously in Lactococcus lactis (14). While LanI and LanFE(G) are known to function in a cooperative manner in several lantibiotic immunity systems (13,15), it has been shown that while the C terminus of NisI is directly involved in nisin binding, it has no role in cooperating with NisFEG (14). The NisFEG ABC transporter is also involved in nisin immunity (16).…”
mentioning
confidence: 99%